Socio-demography of Covid-19 Death in the Special Region of Yogyakarta - Yusni Nuryanti; Liena Sofiana; Trisno Agung Wibowo (Journal of Health Science Community, 2021)
The severity of COVID-19 is influenced by several factors such as endurance, age, sex of the patient and comorbid diseases reported as significant predictors of COVID-19 morbidity and death. The purpose to determine relationship between age and sex with the incidence of death COVID-19. This research a cross-sectional study. The number of study samples was 26,085 confirmed COVID-19 patients. The source of the data used is secondary data obtained from the health office of the Special Region of Yogyakarta. Data analysis used chi square test. The results there was a relationship between age (p= 0.000) (PR= 14,951; 95% CI 11.717-19.074) and sex (p= 0.000) (PR= 1.670; 95% CI 1.442-1.934) with the incidence of death COVID-19. There is a relationship between age and sex with the incidence of death COVID-19.